Raising capsicum in low tunnel is a profitable method - Verma, Arti (Indian Horticulture, 2022)
Increased health awareness, high population growth rate and changing dietary patterns lead to a huge demand of fresh vegetables all round the year in domestic as well as in export market. But as we know, vegetable production is highly influenced by the season and climatic conditions, which results in glut of vegetables during the main season and less profit to the farmers. The time of produce arrival in the market leads to considerable variation in the prices. By adopting low tunnel technology, vegetable growers can advance the crop by about one month than the normal season and get better returns.